A Case of Late Onset Nivolumab-Induced Interstitial Nephritis in a Patient with Metastatic Renal Cell Carcinoma - Hattahara, Kodai (Hinyokika kiyo. Acta urologica Japonica, 2019)
A 43-year-old man underwent nephrectomy for right renal cell carcinoma (cT3aN0M1 (PUL), clear cell carcinoma). Thereafter, he was treated with sunitinib for lung metastases as the first-line therapy for three months. Because lung metastases progressed and new bone metastases appeared, nivolumab was started for the second-line treatment. Although the cancer progression was suppressed by multidisciplinary treatment combined with systemic immunotherapy and local radiation therapy, he developed severe acute kidney injury with cortical swelling after eighteen months of nivolumab treatment. A diagnosis of acute interstitial nephritis induced by nivolumab was made based on biopsy findings. Treatment with prednisolone (1.0 mg/kg daily) led to a rapid improvement in renal function. We must consider the possibility of immunerelated adverse events, especially nivolumab-induced acute kidney injury, even after long-term treatment